Smartphone three-dimensional imaging for body composition assessment using non-rigid avatar reconstruction - Tinsley, Grant M.; Rodriguez, Christian; Florez, Christine M.; Siedler, Madelin R.; Tinoco, Ethan; McCarthy, Cassidy; Heymsfield, Steven B. (Frontiers in Medicine, 2024)
Background: Modern digital anthropometry applications utilize smartphone cameras to rapidly construct three-dimensional humanoid avatars, quantify relevant anthropometric variables, and estimate body composition.In the present study, 131 participants ([73 M, 58 F] age 33.7 ± 16.0 y; BMI 27.3 ± 5.9 kg/m 2 , body fat 29.9 ± 9.9%) had their body composition assessed using dual-energy X-ray absorptiometry (DXA) and a smartphone 3D scanning application using non-rigid avatar reconstruction. The performance of two new body fat % estimation equations was evaluated through reliability and validity statistics, Bland-Altman analysis, and equivalence testing.In the reliability analysis, the technical error of the measurement and intraclass correlation coefficient were 0.5 to 0.7% and 0.996 to 0.997, respectively. Both estimation equations demonstrated statistical equivalence with DXA based on ±2% equivalence regions and strong linear relationships (Pearson's r 0.90; concordance correlation coefficient 0.89 to 0.90). Across equations, mean absolute error and standard error of the estimate values were ~3.5% and ~4.2%, respectively. No proportional bias was observed.While continual advances are likely, smartphone-based 3D scanning may now be suitable for implementation for rapid and accessible body measurement in a variety of applications.